2020
DOI: 10.1038/s41558-019-0687-2
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational epigenetic inheritance in reef-building corals

Abstract: Main 14The notion that intergenerational or transgenerational inheritance operates solely 15 through genetic means is slowly being eroded: epigenetic mechanisms have been shown 16 to induce heritable changes in gene activity in plants 1,2 and metazoans 1,3 . Inheritance of 17 DNA methylation provides a potential pathway for environmentally induced 18 phenotypes to contribute to evolution of species and populations 1-4 . However, in basal 19 metazoans, it is unknown whether inheritance of CpG methylation patter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(72 citation statements)
references
References 53 publications
2
70
0
Order By: Relevance
“…Recent studies on marine invertebrates [reviewed in Eirin-Lopez and Putnam (2019)] have shown that DNA methylation exerts a role on phenotypic acclimatization (Putnam et al, 2016;Liew et al, 2018;Durante et al, 2019) by modulating gene expression (Dixon et al, 2018). Moreover, epigenetic marks acquired throughout the lifespan of coral can be inherited intergenerationally, promoting acclimatized phenotypes in the offspring and thus increasing their fitness (Liew et al, 2020;Putnam et al, 2020). In addition, seasonal patterns of DNA methylation have been observed in vertebrates (Stevenson and Prendergast, 2013;Viitaniemi et al, 2019), invertebrates (Pegoraro et al, 2016;Suarez-Ulloa et al, 2019) and plants (Finnegan et al, 1998;Bastow et al, 2004;Ito et al, 2019).…”
Section: Temporal Differences Dominate Patterns Of Dna Methylationmentioning
confidence: 99%
“…Recent studies on marine invertebrates [reviewed in Eirin-Lopez and Putnam (2019)] have shown that DNA methylation exerts a role on phenotypic acclimatization (Putnam et al, 2016;Liew et al, 2018;Durante et al, 2019) by modulating gene expression (Dixon et al, 2018). Moreover, epigenetic marks acquired throughout the lifespan of coral can be inherited intergenerationally, promoting acclimatized phenotypes in the offspring and thus increasing their fitness (Liew et al, 2020;Putnam et al, 2020). In addition, seasonal patterns of DNA methylation have been observed in vertebrates (Stevenson and Prendergast, 2013;Viitaniemi et al, 2019), invertebrates (Pegoraro et al, 2016;Suarez-Ulloa et al, 2019) and plants (Finnegan et al, 1998;Bastow et al, 2004;Ito et al, 2019).…”
Section: Temporal Differences Dominate Patterns Of Dna Methylationmentioning
confidence: 99%
“…Epigenetic processes that regulate gene expression such as gene methylation are also a mechanism for transgenerational plasticity. While gene methylation has not been directly studied in the context of coral disease yet, studies looking at other stressors such as heat and nutrient addition do show methylation of immune-related adhesion and signaling genes in addition to housekeeping genes (Dimond and Roberts, 2016;Liew et al, 2020). It is important to note that these mechanisms will not benefit all coral species equally, and species that are relatively short-lived and brood their embryos may be better candidates for adaptation due to transgenerational plasticity that could lead to disease resistance, such as Porites astreoides (Pinzon et al, 2014;Fuess et al, 2017).…”
Section: Coral Immune Responses and Their Influences On Diseasementioning
confidence: 99%
“…To successfully conduct SB, adult colonies with relatively high heat tolerances need to be identified and used as broodstock. These colonies can come from different populations exposed to contrasting temperatures profiles at a range of spatial scales (Dixon et al, 2015; Liew et al, 2020; McClanahan et al, 2020), or among individuals from within a single population where there is sufficient intrapopulation variability. While it is well established that coral populations experiencing higher mean SSTs or more variable temperatures tend to be more tolerant to heat stress (Howells et al, 2012; Thomas et al, 2018), less is known about the extent of within-population variation in heat tolerance for corals (Bay and Palumbi, 2014; van Oppen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Competent coral larvae have been seeded en masse onto natural substrates to enhance recruitment (dela Cruz and Harrison, 2017; Doropoulos et al, 2019) and substrates have been designed to settle coral larvae for nursery rearing and outplantation improving early survivorship (Guest et al, 2014; Chamberland et al, 2017). Despite advances in the practice of CLP, most research has focused on the steps during and post-spawning, with little attention given to the provenance or phenotype of the broodstock colonies (apart from laboratory based studies e.g., Dixon et al, 2015; Liew et al, 2020; Quigley et al, 2020). To the best of our knowledge, there have been no attempts to select parents for adaptive traits, such as heat tolerance, as part of CLP for reef rehabilitation.…”
Section: Introductionmentioning
confidence: 99%